ChemInform Abstract: Copper‐Catalyzed Asymmetric Alkylation of β‐Keto Esters with Xanthydrols. Issue 19 (13th May 2014) - Trillo, Paz; Baeza, Alejandro; Najera, Carmen
Abstract The novel green process produces water as the only by‐product and is applied to a wide range of keto esters.